Changes in pressure waves after endoscopic intervention in patients with achalasia: A focus on peristaltic recovery of the esophageal body - Se Kyung Park; Su Jin Hong; Jae Pil Han; Hyeon Jeong Goong; Hyun Soo Kim; Yu Sik Myung; Shin Hee Kim; Hee Jae Jung; Tae Hee Lee; Joon Seong Lee; et al. (Turkish Journal of Gastroenterology, 2019)
Background/Aims: We conducted the present study to investigate the recovery of peristalsis of the esophageal body and evaluate the pressure changes observed on manometry before and after endoscopic intervention. Materials and Methods: Forty-five patients were diagnosed with achalasia, and 36 received endoscopic or surgical treatment. We collected the data of 24 patients who underwent manometry before and after treatment (pneumatic balloon dilatation, n=7; botulinum toxin injection, n=10; peroral endoscopic myotomy, n=7). Results: The lower esophageal sphincter (LES) resting pressure and nadir LES relaxation pressure decreased regardless of the achalasia subtype or type of endoscopic intervention following treatment (p<0.05). Among patients with a nadir LES relaxation pressure of <4 mmHg, 42.9% (6/14) exhibited partial esophageal peristaltic wave recovery. However, no patients with a nadir LES relaxation pressure of >4 mmHg exhibited peristaltic wave recovery (p=0.024). Of the six patients with peristaltic wave recovery, two had type I achalasia (15.4%), three had type II (33.3%), and one had type III (100.0%). The Eckardt score, symptom duration, and type of intervention were not associated with the recovery of peristaltic waves. Conclusion: Our results suggest that normalization of the nadir LES relaxation pressure can be a predictive factor for the recovery of esophageal peristalsis.